The forests of silence - Rodda, Emily (New York : Scholastic, 2001)
The evil Shadow Lord is planning to take over the land of Deltora and enslave all its people. In order to stop him 16-year old Lief and former palace guard Barda must find all seven stones from the magic belt of Deltora.
RL 4.
008-012.
Keywords: Magical thinking -- Fiction; Magic -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Magic -- Fiction